Avaliação dos parâmetros cardiovasculares em pacientes submetidos à sedação consciente com óxido nitroso - Ferreira, José Divino Bezerra (2007)
Fear is a fundamental human emotion. It is fear that triggers physiological responses that prepare the body for action against real or imaginary threats, allowing the individual to decide whether to fight or flee. When fear, or resulting anxiety, interferes with the provision of healthcare causing patients to delay or avoid care, it is necessary to take measures to eliminate or minimize this feeling. Even today, patients avoid dental care due to fear or anxiety. To those, classified as “phobic”, are added patients with special needs and non-cooperative children. In these cases, hypnotic and anxiolytic drugs have been used, as well as general anesthesia. As an alternative to the use of such drugs, the mixture of nitrous oxide and oxygen, also called conscious sedation or inhalation analgesia, have been used throughout the world with a high degree of success. The objective of this study was to perform a comparative analysis of cardiovascular parameters and pulse oximetry values in two groups of 20 patients, classified as ASA I and II according to the American Society of Anesthesiologists (ASA) classification, who were referred for surgical removal of impacted third molars. Patients in the experimental group (n=20) underwent surgery under local anesthesia with sedation consisting of 70% nitrous oxide and 30% oxygen, while patients in the control group (n=20) underwent the same surgical procedure but only under local anesthesia. The results demonstrated that sedation with 70% nitrous oxide is a safe and effective procedure. The cardiovascular parameters in the group given sedation showed more hemodynamic stability than those observed in the group that only received local anesthesia. In none of the groups, desaturation episodes or electrocardiographic changes of clinical significance were observed.